EXTH-11. TELOMERASE INHIBITION IS AN EFFECTIVE THERAPEUTIC STRATEGY IN TERT PROMOTER-MUTANT GLIOBLASTOMAS MODELS WITH LOW TUMOR BURDEN. (14th November 2022) - Kageler, Lauren; Aquilanti, Elisa; Watson, Jacqueline; Baird, Duncan; Jones, Rhiannon; Hodges, Marie; Wen, Patrick Y; Meyerson, Matthew
Abstract: Glioblastoma targeted therapeutics have been challenging to develop due to significant inter- and intra-tumoral heterogeneity. While many activated oncogenes in glioblastoma are subclonal, TERT promoter mutations commonly occur as clonal events and are found in up to 80% of IDH-wildtype glioblastomas. Given the high prevalence and clonal nature of TERT promoter mutations in glioblastoma, telomerase is considered a promising therapeutic target for this deadly cancer. Prior studies have validated this hypothesis, demonstrating that knockout of the transcription factor GABPA, which selectively binds to the mutant TERT promoter, as well as base editing-mediated correction of TERT promoter mutations, are selectively toxic to TERT promoter mutant glioblastomas. However, an important limitation of this strategy is that cancer cell death does not occur immediately after telomerase ablation, but rather after several cell divisions required to reach critically short telomeres. We therefore hypothesize that telomerase inhibition would only be effective in low tumor burden glioblastomas. In this study, we used CRISPR interference to knock down TERT expression in TERT promoter-mutant glioblastoma cell lines and patient derived models. We then measured cell viability and assessed for features of telomere crisis by measuring telomere length and chromatin bridge formation. Lastly, we used a doxycycline inducible CRISPR interference system to knock down TERT expression in vivo early and late in the tumor formation process. We demonstrated that TERT promoter-mutant glioblastoma cells are sensitive to telomerase inhibition and undergo telomere crisis. In vivo, tumor formation is only inhibited when TERT knockdown is induced shortly after tumor implantation, but not when tumor burden is high. This work supports the idea that telomerase inhibition would be a suitable therapeutic strategy for glioblastoma patients with low tumor burden, for example in the adjuvant setting after surgical debulking and chemoradiation.